2018
DOI: 10.1159/000490419
|View full text |Cite
|
Sign up to set email alerts
|

Effective Desensitization to Tocilizumab in Delayed Hypersensitivity Reaction

Abstract: We present tocilizumab desensitization of a 47-year-old woman affected by rheumatoid arthritis with full body delayed erythematous urticarial reaction. Skin test for tocilizumab gave cutaneous reaction after 6 h at 20 mg/mL. The schedule of desensitization was then adapted for non-immediate reaction. We prepared a desensitization procedure reaching the cumulative dose of 516 mg in 5 weeks. After 6 months, the repetition of skin tests had a negative result, with demonstration of tolerance induction. Today the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 9 publications
(8 reference statements)
0
12
0
2
Order By: Relevance
“…Regarding NIHRs, cases of nonimmediate urticaria, 141 DRESS, 142,143 SJS, 144 and AGEP 145 were reported. Younger age, shorter stature, lighter weight, and increased disease activity in the early period of tocilizumab administration have been identified as risk factors for DHRs 146 …”
Section: Anti‐cytokine/anti‐inflammatory Drugs Used For Mas/cytokine mentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding NIHRs, cases of nonimmediate urticaria, 141 DRESS, 142,143 SJS, 144 and AGEP 145 were reported. Younger age, shorter stature, lighter weight, and increased disease activity in the early period of tocilizumab administration have been identified as risk factors for DHRs 146 …”
Section: Anti‐cytokine/anti‐inflammatory Drugs Used For Mas/cytokine mentioning
confidence: 99%
“…Only one study revealed that STs have a low negative predictive value in NIHR 140 . Desensitization to tocilizumab in NIHRs was effectively applied in a weekly scheme with premedication in one case 141 . Rapid drug desensitization is successfully and routinely used for IHRs 19,134 (Table 3).…”
Section: Anti‐cytokine/anti‐inflammatory Drugs Used For Mas/cytokine mentioning
confidence: 99%
“…A recent publication proved that desensitization is a safe and cost-effective procedure [3]. Desensitization to drugs used in rheumatology such as TNF blockers , rituximab [8,15,18,19,[30][31][32][33][34][35][36][37][38][39][40][41][42], tocilizumab [43][44][45][46][47][48], IL-17 blockers (ixekizumab) [49] and anti-IL-1 (anakinra) [50][51][52][53] has been described. Most of the described procedures were performed in patients with rheumatoid arthritis [8,32] but desensitization in patients with lupus or spondyloarthropathies [24], adult-onset Still disease [43], IgG4-related disease [40] and autoinflammatory disorders [51][52][53] has also been performed with success.…”
Section: Medical Indicationsmentioning
confidence: 99%
“…Most of the described procedures were performed in patients with rheumatoid arthritis [8,32] but desensitization in patients with lupus or spondyloarthropathies [24], adult-onset Still disease [43], IgG4-related disease [40] and autoinflammatory disorders [51][52][53] has also been performed with success. In most of the published cases desensitization was performed in patients with immediate reactions, but single reports on successful desensitization in delayed reactions [47] and serum sickness disease (type III reaction) [34] have been published as well. Table I presents the published cases of desensitization to biological agents used in rheumatic diseases.…”
Section: Medical Indicationsmentioning
confidence: 99%
“…Allergological study: Cutaneous testing with tocilizumab is usually performed at 20 mg/ml for the prick-test and 0.2 mg/ml [29], 20 mg/ml [52] or 2 mg/ml [49,53] for the intradermal test. If skin tests are negative, a DPT can be performed after evaluating the risk-benefit ratio and switching to a subcutaneous route can be considered [49].…”
Section: Rationale: Studies Conducted In Patients Who Died Of Sars Anmentioning
confidence: 99%